Understanding stem cell immunogenicity in therapeutic applications - Wood, K; Issa, F; Hester, J (Cell Press, 2015)
Stem cells and their differentiated progeny offer great hope for treating disease by providing an unlimited source of cells for repairing or replacing damaged tissue. Initial studies suggested that, unlike 'normal' transplants, specific characteristics of stem cells enabled them to avoid immune attack. However, recent findings have revealed that the immunogenicity of stem cells may have been underestimated. Here, we review the current understanding of the mechanisms of immune recognition associated with stem cell immunogenicity, and discuss the relevance of reprogramming and differentiation strategies used to generate cells or tissue from stem cells for implantation in eliciting an immune response. We examine the effectiveness of current strategies for minimising immune attack in light of our experience in the transplantation field and, in this context, outline important challenges moving forward.